The rise of the body bots [robotic exoskeletons]. - Guizzo, E.
This paper discusses the current status of the research and development on robotic exoskeletons for both commercial and military applications in Japan and the US. Designed to help elderly and disabled people walk, climb stairs, and carry things around, the Japanese exoskeleton, called HAL-5, is set to hit the market in November 2005. Meanwhile, in the US, the most advanced exoskeleton projects are currently underway at the University of California and at Sacros Research Corp. Both groups are working on a second-generation exoskeleton that is a huge improvement over its predecessor. These projects appear to be the first of a platoon of considerably more capable exoskeletons aimed at real-world uses that may soon become part of the mainstream. While most of these systems are designed for the physically weak or disabled people, researchers are quick to mention other commercial possibilities including their use for rescue and emergency operations, moving furniture and other heavy objects, and even construction work.
Keywords: HAL-5.; Body bots; Brute force; Decision-making.; Dexterity; Emergency personnel; Exoskeletons; Rescue personnel; Robotic exoskeletons